PEMODELAN BAWAH PERMUKAAN MANIFESTASI MINERAL DENGAN METODE GEOMAGNETIK DAERAH PACITAN JAWA TIMUR - Fatimah Fatimah (KURVATEK, 2019)
Tulakan Subdistrict, Pacitan Regency, East Java Province. This area is part of the Southern Mountain Zone of East Java, which is the Sunda-Banda magmatic arc of Oligo-Miocene age, where there are alterations and indications of valuable ore minerals. Field magnetic data is taken in an area of 1 x 1 km, with the looping method on the grid trajectory within 200 x 100 m. Then, magnetic data correction and data processing were carried out with Oasis Montaj. From the magnetic anomaly map, the value of high magnetic intensity in the southern part is fresh (intrusive) andesit-dasitic rock as host rock which causes alteration, in the middle has a low magnetic intensity value which is in the direction of the relatively NE-SW river direction, whereas in the north with high intensity is fresh andesite lava. From the image data, it can be seen that the straightness pattern of the geological structure which is dominated by the extensional structure with the direction of NE-SW and E-W is the main trap of epithermal veins carrying ore mineralization mainly Cu, Pb in the study area.